Effect of Polyethylene Glycol (PEG) & Polyvinyl Alcohol (PVA) Concentrations on the Mechanical Behavior and Microstructure of Sintered Hydroxyapatite for Biomedical Use - Mohamad Hafeezudin Mustafa Kamal Pasha; Noor Hakim Rafai (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The increasing number of road accidents has led to a growing demand for effective bone repair materials. Hydroxyapatite (HAp), a bioceramic that closely resembles the mineral component of natural bone, is widely used for this purpose. To enhance its mechanical properties, water-soluble binders such as polyethylene glycol (PEG) and polyvinyl alcohol (PVA) are commonly incorporated into HAp. This study was conducted with three main objectives: to characterise the fundamental material properties of Hydroxyapatite (HAp), to examine the role of binder composition (specifically PEG and PVA) in the fabrication of HAp composites, and to assess the mechanical properties of HAp composites with varying binder concentrations. Four samples were prepared using dry mixing and compaction methods, with PEG and PVA concentrations ranging from 1% to 5% by weight. Among the prepared samples, Sample 3—containing 3% PEG and 3% PVA—demonstrated the best overall performance. It exhibited high hardness (515.998 HV), moderate porosity (5.6467%), excellent yield strength (16.1356 N/mm²), and a strong crystalline structure, indicated by an intensity count of 2100. These findings reveal that the ratio of PEG to PVA significantly affects the mechanical strength, porosity, and surface quality of HAp composites, making Sample 3 particularly promising for bone replacement applications.